2016
DOI: 10.1038/modpathol.2016.35
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of 8q24/MYC rearrangement in chronic lymphocytic leukemia

Abstract: Chromosome 8q24/MYC rearrangement is associated with Burkitt lymphoma and some aggressive B-cell lymphomas, but is rare in chronic lymphocytic leukemia. We here report a cohort of 20 chronic lymphocytic leukemia patients with 8q24/MYC rearrangement, 3 detected at time of initial diagnosis and 17 acquired after a median interval of 48 months. At the time when 8q24/MYC arrangement was detected, 18 patients had B-symptoms, 17 had lymphadenopathy, and 17 had splenomegaly. Histologically, typical chronic lymphocyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…MYC rearrangements in CLL are also associated with histological progression or large cell transformation (Richter syndrome) (Fabbri et al, 2011; Li et al, 2016; Rossi et al, 2011). NOTCH1 mutations and MYC rearrangements tend to be mutually exclusive in Richter syndrome (Fabbri et al, 2011), suggesting that both may serve to produce sustained MYC expression.…”
Section: Discussionmentioning
confidence: 99%
“…MYC rearrangements in CLL are also associated with histological progression or large cell transformation (Richter syndrome) (Fabbri et al, 2011; Li et al, 2016; Rossi et al, 2011). NOTCH1 mutations and MYC rearrangements tend to be mutually exclusive in Richter syndrome (Fabbri et al, 2011), suggesting that both may serve to produce sustained MYC expression.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of c-MYC rearrangement in CLL/SLL varies greatly in different studies. Nelson et al showed no c-MYC rearrangement by FISH in 109 cases of CLL/SLL [156], and Li et al identified 0.7% CLL/SLL with 8q24/MYC rearrangement in approximately 4500 cases [157]. In Li鈥檚 study, c-MYC is most frequently rearranged with immunoglobulin heavy chain gene locus in the t(8;14)(q24路1;q32), followed by light chain loci in t(8;22)(q24路1;q11路2), or t(2;8)(p12;q24路1).…”
Section: C-myc In Low Grade B-cell Lymphomasmentioning
confidence: 99%
“…In Li鈥檚 study, c-MYC is most frequently rearranged with immunoglobulin heavy chain gene locus in the t(8;14)(q24路1;q32), followed by light chain loci in t(8;22)(q24路1;q11路2), or t(2;8)(p12;q24路1). c-MYC rearrangement in CLL/SLL is often acquired during the course of disease and is associated with increased prolymphocytes or Richter鈥檚 transformation [157,158]. c-MYC rearrangement is frequently seen with concomitant adverse cytogenetic markers of CLL/SLL, such as del(11q) and/or del(17p)/monosomy 17, which helps explain the poor clinical outcomes in these patients [159].…”
Section: C-myc In Low Grade B-cell Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Absence of del(13q14) also has been associated with an increased risk for transformation to RS. Rearrangements involving the MYC locus (8q24), very rare in CLL/SLL, may be gained during the course of disease, and have been suggested as a secondary event in disease progression, particularly in patients who harbor 8q24/MYC rearrangement in the context of a complex karyotype [12,38]. Another possible mechanism of MYC involvement in CLL/ SLL, also associated with a shorter clinical course, is 8q24/MYC amplification.…”
Section: Histologic Variants Of Richter Transformationmentioning
confidence: 99%